Association between Socio-demographic, Nutrition Intake, Cultural Belief, and Incidence of Anemia in Pregnant Women In Karanganyar, Central Java - Sinawangwulan, Indah Permatasari; Dewi, Yulia Lanti Retno; Wekadigunawan, CSP. (Journal of Maternal and Child Health, 2018)
Background: Anemia in pregnancy remains a major public health issue in developing countries. Studies in Indonesia examining the effects of socio-demographic factors, dietary pattern, and cultural belief on the risk of anemia in pregnancy are lacking. This study aimed to examine the effects of socio-demographic factors, dietary pattern, and cultural belief on the risk of anemia in pregnancy.Subjects and Method: An analytic cross-sectional study was conducted in 5 community health centers in Karanganyar, Central Java, from February to March 2018.A total of 200 trimesters I, II, and III pregnant mothers was selected for this study by fixed disease sampling, consisting of 50 mothers with anemia and 150 mothers without anemia. The dependent variable was anemia during pregnancy. The independent variables were nutrition intake, dietary pattern, consumption of iron tablet, family income, parity, family size, antenatal care visit, and cultural belief. The data were collected by questionnaire. The anemia status was obtained from the medical record. The data were analyzed by path analysis performed on Stata 13.Results: The risk of anemia during pregnancy directly decreased with better nutrition intake (b= -1.02; 95% CI= -1.73 to -0.31; p= 0.005) and regular consumption of iron tablet (b= -0.79; 95% CI= 1.48 to -0.10; p= 0.024). The risk of anemia during pregnancy was indirectly affected by better dietary pattern, higher family income, larger family size, cultural belief, parity, higher education, and antenatal care visit.Conclusion: Good nutrition intake and regular consumption of iron tablet decreased the risk of anemia during pregnancy. Dietary pattern, family income, family size, cultural belief, parity, and maternal education have indirect effects on the risk of anemia during pregnancy.Keywords: anemia, pregnancy, nutrition intake, iron tablet, dietary patternCorrespondence: Indah Permatasari Sinawangwulan. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: siindahnawang@gmail.com. Mobile: +6285655261261.Journal of Maternal and Child Health (2018), 3(2): 128-137https://doi.org/10.26911/thejmch.2018.03.02.05